Cilji omejene epistemske racionalnosti - Tomat, Nastja (Analiza (Ljubljana), 2024)
Notions of rationality in epistemology are often based on idealised models of epistemic agents and the environment in which they are embedded. The concept of bounded epistemic rationality aims to avoid such idealizations and proposes norms of inquiry based on empirical data about the limitations of human cognition and the features of the epistemic environment. Drawing on Simon's work on bounded rationality, Gigerenzer's notion of ecological rationality, and McKenna's programme of non-ideal epistemology, it functions as a hybrid concept that contains both normative and descriptive elements and offers epistemic advice that helps to improve our epistemic position and achieve our epistemic goals. Traditionally, epistemic goals include forming true beliefs and avoiding false beliefs, justification, knowledge, and understanding. In this paper, I summarise selected aspects of the debate about epistemic values and goals, focusing on veritistic monism, and reflect on the goals of bounded epistemic rationality. I conclude that bounded epistemic strives towards various forms of cognitive success, not only towards the truth, but limits rational inquiry to questions relevant to the epistemic agent.
Keywords: epistemic goals; epistemic values; epistemologija; epistemology; epistemske vrednosti; epistemski cilji; filozofija; philosophy; racionalnost; rationality